2021
DOI: 10.2147/ccid.s342401
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Chronic Actinic Dermatitis with Dupilumab: A Case Report and Review of the Literature

Abstract: Chronic actinic dermatitis (CAD) is a rather rare photosensitive disease characterized by a persistent eczematous eruption in sun-exposed sites. The pathogenesis of CAD has not been completely elucidated. The clinical treatment of CAD is still challenging and not standardized. Some patients with severe CAD have achieved satisfactory clinical results with dupilumab when conventional therapies have failed. We herein report the case of a 45-year-old male with severe CAD who responded rapidly to combined treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Dupilumab is an IL-4 receptor alpha antagonist that blocks Th2 proinflammatory cytokines IL-4 and IL-13. Although previous reports [8][9][10][11][12][13] and this study have found that dupilumab showed surprising efficacy in the treatment of CAD, it is challenging to speculate on the exact mechanism of dupilumab to improve the disease severity in patients with CAD. Ko et al found the role of Th1/Th2 misbalance in patients suffering severe CAD.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Dupilumab is an IL-4 receptor alpha antagonist that blocks Th2 proinflammatory cytokines IL-4 and IL-13. Although previous reports [8][9][10][11][12][13] and this study have found that dupilumab showed surprising efficacy in the treatment of CAD, it is challenging to speculate on the exact mechanism of dupilumab to improve the disease severity in patients with CAD. Ko et al found the role of Th1/Th2 misbalance in patients suffering severe CAD.…”
Section: Discussionmentioning
confidence: 56%
“…8,9 In the literature review, adverse events occurred in 33.33% (4/12) of patients after treatment of dupilumab and presented by dupilumab facial redness and conjunctivitis. [8][9][10][11][12][13] Only one of our patients experienced an injection site reaction at the first injection, and it was resolved within 3 hours after oral antihistamine.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Chronic photodermatoses including chronic actinic dermatosis (CAD) and actinic prurigo are induced by exposure to UV-radiation and can resemble photosensitive AD. Reports showed efficacy of dupilumab in 16 cases of CAD ( Table 8 ) [ 252 , 253 , 254 , 255 , 256 , 257 , 258 ] as well as in a pediatric patient with actinic prurigo [ 259 ], leading to higher minimal erythema doses in repeated UV-phototesting in some cases.…”
Section: Resultsmentioning
confidence: 99%